2012
DOI: 10.1038/nbt.2214
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of affinity, specificity and function of designed influenza inhibitors using deep sequencing

Abstract: We show that comprehensive sequence-function maps obtained by deep sequencing can be used to reprogram interaction specificity and to leapfrog over bottlenecks in affinity maturation by combining many individually small contributions not detectable in conventional approaches. We use this approach to optimize two computationally designed inhibitors against H1N1 influenza hemagglutinin and, in both cases, obtain variants with subnanomolar binding affinity. The most potent of these, a 51-residue protein, is broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
374
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 360 publications
(382 citation statements)
references
References 42 publications
8
374
0
Order By: Relevance
“…In Stage 4, like some previous DMS efforts (Doud & Bloom, 2016), we directly sequenced the coding region from the clone population to determine variant frequency before and after selection. Use of tiled amplicons enables individual template molecules to be sequenced on both strands, allowing elimination of most base‐calling errors (Fowler et al , 2010; Whitehead et al , 2012; Zhang et al , 2016) (see Materials and Methods for details). This reduction in base‐calling error allows us to more accurately measure lower allele frequencies in mutagenized libraries.…”
Section: Resultsmentioning
confidence: 99%
“…In Stage 4, like some previous DMS efforts (Doud & Bloom, 2016), we directly sequenced the coding region from the clone population to determine variant frequency before and after selection. Use of tiled amplicons enables individual template molecules to be sequenced on both strands, allowing elimination of most base‐calling errors (Fowler et al , 2010; Whitehead et al , 2012; Zhang et al , 2016) (see Materials and Methods for details). This reduction in base‐calling error allows us to more accurately measure lower allele frequencies in mutagenized libraries.…”
Section: Resultsmentioning
confidence: 99%
“…Of special interest, it has been demonstrated that mutations of non-contacting residues near the interface of a protein-protein interaction can enhance the electrostatic charge complementarity resulting in improved affinity, specifically by reducing the k off rate. 29,30
10.1080/19420862.2018.1490119-F0002Figure 2.Molecular interaction of key residues of the designed Fc variants. An interaction map was calculated using the Rosetta REF2015 score function to define the energy of interaction between residues.
…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the designed binding mode and identify possible avenues for improving the computational design, we used PCR mutagenesis in concert with one round of fluorescent-activated cell sorting (FACS) and next-generation sequencing, resulting in a fine-resolution map of the sequencefunction landscape (18,19). Sequencing of the C-terminal 51 positions, which contain the designed binding site, was carried out before and after selection for IgG binding.…”
Section: Resultsmentioning
confidence: 99%